Functional characterization and application of a tightly regulated MekR/[P.sub.mekA] expression system in Escherichia coli and Pseudomonas putida - Graf, Nadja; Altenbuchner, Josef (Applied microbiology and biotechnology, 2013)
A methyl ethyl ketone (MEK)-inducible system based on the broad-host-range plasmid pBBR1MCS2 and on the [P.sub.mekA] promoter region of the MEK degradation operon of Pseudomonas veronii MEK700 was characterized in Escherichia coli JM109 and Pseudomonas putida KT2440. For validation, β-galactosidase (lacZ) was used as a reporter. The novel system, which is positively regulated by MekR, a member of the AraC/XylS family of regulators, was shown to be subject to carbon catabolite repression by glucose, which, however, could not be attributed to the single action of the global regulators Crc and PtsN. An advantage is its extremely tight regulation accompanied with three magnitudes of fold increase of gene expression after treatment with MEK. The transcriptional start site of [P.sub.mekA] was identified by primer extension, thereby revealing a potential stem-loop structure at the 5' end of the mRNA. Since MekR was highly insoluble, its putative binding site was identified through sequence analysis. The operator seems to be composed of a 15-bp tandem repeat (CACC[N.sub.5]CTTCAA) separated by a 6-bp spacer region, which resembles known binding patterns of other members of the AraC/XylS family. Subsequent mutational modifications of the putative operator region confirmed its importance for transcriptional activation. As the -35 promoter element seems to be overlapped by the putative operator, a class II activation mechanism is assumed.